2023
DOI: 10.1101/2023.02.19.529127
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FALCON systematically interrogates free fatty acid biology and identifies a novel mediator of lipotoxicity

Abstract: Cellular exposure to free fatty acids (FFA) is implicated in the pathogenesis of obesity-associated diseases. However, studies to date have assumed that a few select FFAs are representative of broad structural categories, and there are no scalable approaches to comprehensively assess the biological processes induced by exposure to diverse FFAs circulating in human plasma. Furthermore, assessing how these FFA-mediated processes interact with genetic risk for disease remains elusive. Here we report the design an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 177 publications
(226 reference statements)
0
11
0
Order By: Relevance
“…This phenomenon was directly mitigated by oleate, and impeding the conversion of stearate to oleate ampli ed the cytotoxic effects of stearate. Wieder et al 5 segregated longchain fatty acid-elicited cellular damage into two major pathways, UPR and ROS generation, and showed that the detrimental effects associated with UPR could be rescued by oleate treatment. Our results corroborate the aforementioned ndings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon was directly mitigated by oleate, and impeding the conversion of stearate to oleate ampli ed the cytotoxic effects of stearate. Wieder et al 5 segregated longchain fatty acid-elicited cellular damage into two major pathways, UPR and ROS generation, and showed that the detrimental effects associated with UPR could be rescued by oleate treatment. Our results corroborate the aforementioned ndings.…”
Section: Discussionmentioning
confidence: 99%
“…However, fatty acids are not universally detrimental, and their effects on cancer cells vary depending on the type of fatty acid 5 .…”
Section: Introductionmentioning
confidence: 99%
“…While many important questions remain, we propose that the PAQR proteins constitute a promising type of target for pharmacological intervention to remedy membrane composition defects that are associated with numerous pathologies, including cancer [ 107 ] and diabetes. [ 110 ]…”
Section: Discussionmentioning
confidence: 99%
“…In certain disease contexts, astrocytes can take on a reactive state that is toxic to neurons and oligodendrocytes (Liddelow et al, 2017). The precise identity and source of the toxicity remains to be determined and is likely context dependent, but there is evidence that the ceramide synthesis pathway could be involved (Arredondo et al, 2022; Chung et al, 2023; Guttenplan et al, 2021; Victor et al, 2022; Wieder et al, 2023). This is consistent with evidence that glial cells can produce saturated lipids (sphingolipids?)…”
Section: Discussionmentioning
confidence: 99%